Friedel–Crafts Reaction of Benzyl Fluorides: Selective Activation of CF Bonds as Enabled by Hydrogen Bonding1. Issue 50 (10th October 2014) - Champagne, Pier Alexandre; Benhassine, Yasmine; Desroches, Justine; Paquin, Jean‐François
Abstract A Friedel–Crafts benzylation of arenes with benzyl fluorides has been developed. The reaction produces 1, 1‐diaryl alkanes in good yield under mild conditions without the need for a transition metal or a strong Lewis acid. A mechanism involving activation of the CF bond through hydrogen bonding is proposed. This mode of activation enables the selective reaction of benzylic CF bonds in the presence of other benzylic leaving groups.